Advances in Barley Breeding for Improving Nitrogen Use Efficiency - Zhiwei Chen; Luli Li; Nigel G. Halford; Hongwei Xu; Linli Huang; Runhong Gao; Ruiju Lu; Chenghong Liu (Agronomy, 2022)
Crop breeding for high nitrogen use efficiency (NUE) or tolerance to low nitrogen fertilization is thought to be an ideal solution to reduce the cost, carbon footprint, and other environmental problems caused by the excess use of nitrogen fertilizers. As a model plant for cereal crops, barley has many advantages, including good adaptability, a short growth period, and high natural stress resistance or tolerance. Therefore, research on improving NUE in barley is not only beneficial for nitrogen-efficient barley breeding but will also inform NUE improvement in other cereal crops. In this review, recent progress in understanding barley’s response to nitrogen nutrition, evaluation of NUE or low-nitrogen tolerance, quantitative trait loci (QTL) mapping and gene cloning associated with improving NUE, and breeding of nitrogen-efficient barley is summarized. Furthermore, several biotechnological tools that could be used for revealing the molecular mechanisms of NUE or breeding for improving NUE in barley are introduced, including GWAS, omics, and gene editing. The latest research ideas in unraveling the molecular mechanisms of improving NUE in other crops are also discussed. Thus, this review provides a better understanding of improving the NUE of barley and some directions for future research in this area.